The Influence of Learning Aqidah Akhlak with Game Methods on Student Behavior at Miftahul Ihsan Elementary School - Yulianingsih; Dewi, Yumna; Zuhriya, Yulidatus; Yunani; Yusmalinar (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to examine the effect of learning Aqidah Akhlak with the game method on student behavior at Madrasah Ibtidaiyah Miftahul Ihsan. Learning Aqidah Akhlak presented through a game method approach is believed to be able to improve students' understanding of moral and religious values ​​more enjoyable and effective. The educational game method not only teaches material theoretically, but also actively involves students in the learning process, so that they can more easily understand and apply the teachings in everyday life. This study uses a quantitative design with an experimental method. The sample taken was grade V students of Madrasah Ibtidaiyah Miftahul Ihsan who were divided into two groups, namely the experimental group that received learning with the game method and the control group that followed conventional learning. Data collection was carried out through observation, questionnaires, and interviews to measure changes in student behavior in the aspects of morals, morals, and social. The results of the study showed a significant influence between learning Aqidah Akhlak with the game method on student behavior. Students who follow learning with the game method show better improvements in terms of mastery of moral values, discipline, and positive social behavior. The educational game method has proven to be more effective in making students interested and easier in understanding and applying Aqidah Akhlak lessons in everyday life. This research is expected to contribute to the development of learning methods in madrasas, especially in the application of character education through a fun and interactive approach. Thus, it is expected to produce a generation that is not only intelligent in religious knowledge, but also behaves well in accordance with the teachings of Islamic morals